PENGARUH MODEL POLYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V SD - Riastini, Pt. Nanci; Mustika, I Kd. Agus (International Journal of Elementary Education, 2017)
This study aimed at investigating different performances in solving mathematical problems of fifth grade students who attends learning process in polya model and students who attends learning process which not used polya model in Cluster I Airlangga Mendoyo Sub-district in academic year 2016/2017. This study was a quasi-experimental research that is post-test only control group design. The population of this study was all of fifth grade students of elementary school in Cluster I Airlangga Mendoyo Sub-district. The population of the study consisted of eleven classes with 183 students. Random sampling technique was used to determine the sample of the study. The data collection was conducted through test. The instrument of the data collection was essay test. The data collected through test was analyzed descriptively to find out the mean, median, mode and inferentially by conducting t-test (polled variance). The result of hypothesis testing shows that there is significant difference of students’ ability in solving mathematical problem between students who attend learning process in polya model and students who attend a learning process which not use polya model. The finding indicates that learning process in polya model make students to actively participate in discussion to solve mathematical problem presented. Furthermore, the phases of polya model train students to work systematically in solving the problem. Thus, polya model give significant effect on fifth grade students’ ability in solving mathematical problem in Cluster I Airlangga Mendoyo Sub-district in academic year 2016/2017.